Human Trafficking Issue in ASEAN Countries: A Discussion to Overcome - Mohammad, Nhelbourne; Islahuddin, Islahuddin; Setiyani, Ratna Yunita; Sulisworo, Dwi (Lembaga Jurnal dan Publikasi Universitas Muhammadiyah Buton, 2023)
Human trafficking is a significant issue in ASEAN countries and across the world, characterized by the exploitation and abuse of individuals for forced labor and sexual exploitation. To overcome this issue, various policies and strategies have been adopted by the United Nations and many countries. However, the effectiveness of these efforts is difficult to measure due to the hidden and often under-reported nature of human trafficking. In ASEAN countries, there have been some steps taken to address this issue, such as the adoption of the ASEAN Convention against Trafficking in Persons, but much more needs to be done to effectively address this persistent problem. Addressing human trafficking requires a coordinated and sustained effort from governments, civil society organizations, and the international community as a whole. The implementation and impact of these policies and strategies must be closely monitored and evaluated to ensure their effectiveness in addressing human trafficking in ASEAN countries and beyond